SDG's UPI 2023 thematic KKN journey in Garawangi village: Devotion, collaboration, and Memories - Mohammad Firos Anggarda; Muhamad Zaidan Rizqita (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
The SDG's UPI 2023 Thematic KKN Program in Garawangi Village aims to provide direct benefits for students in developing skills and practical experience while positively impacting the local community. Through teaching activities in elementary schools, students' understanding of lesson concepts increases. Jamboree activities, health education, and competitions provide village communities with additional knowledge, experience, and a spirit of collaboration. With active student participation and cooperation with village heads, this program has created a mutually beneficial learning environment, positively contributing to sustainable development in Garawangi Village. This service program has succeeded in positively impacting and significantly contributing to society. By increasing community participation in activities supporting SDG achievement, students are actively involved in teaching at elementary schools, jamboree activities, health education, and organizing competitions in RW 05 Garawangi Village. Students and village communities benefit from this program, creating a mutually beneficial and synergistic learning environment between academics and village government.   Abstrak Tujuan dari Program KKN Tematik SDG's UPI 2023 di Desa Garawangi untuk memberikan manfaat langsung bagi mahasiswa dalam pengembangan keterampilan dan pengalaman praktis, sementara juga membawa dampak positif bagi masyarakat setempat. Melalui kegiatan pengajaran di Sekolah Dasar, terjadi peningkatan pemahaman siswa terhadap konsep-konsep pelajaran. Kegiatan jambore, penyuluhan kesehatan, dan lomba memberikan masyarakat desa pengetahuan tambahan, pengalaman, dan semangat kolaborasi. Dengan melibatkan partisipasi aktif mahasiswa dan kerjasama dengan kepala desa, program ini berhasil menciptakan lingkungan belajar yang saling menguntungkan, memberikan kontribusi positif bagi pembangunan berkelanjutan di Desa Garawangi. Program pengabdian ini berhasil memberikan dampak positif dan kontribusi signifikan bagi masyarakat. Dengan peningkatan partisipasi masyarakat dalam kegiatan-kegiatan yang mendukung pencapaian SDG’s, mahasiswa terlibat aktif dalam mengajar di Sekolah Dasar, kegiatan jambore, penyuluhan kesehatan, dan mengorganisir lomba di RW 05 Desa Garawangi. Mahasiswa dan masyarakat desa sama-sama mendapatkan manfaat dari program ini, menciptakan lingkungan belajar yang saling menguntungkan dan sinergis antara akademisi dan pemerintah desa. Kata Kunci: KKN; KKN Tematik SDG’s UPI; SDGs